PERANCANGAN SIMRS FLEKSIBEL UNTUK MENINGKATKAN KINERJA RUMAH SAKIT DAN KLINIK PELAYANAN KESEHATAN - Anggun Nugroho; Ratna Kartika Wiyati; Indrianto . (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTInformation is the basis for policymaking, planning, programming, and accountability. Health informatics is the integration of information science, computer science, and health care. This system deals with the resources, tools, and methods needed to optimize data collection, storage, processing and use of information in the health and biomedical fields. Boddy et. al (2005) describe information systems as